South Africa: Coping with structural changes - Liebenberg, Frikkie; Kirsten, Johann F. (International Food Policy Research Institute, 2006)
Analyzing the evolution of agricultural research and development policy in South Africa is a fascinating but difficult task, primarily because of the large number of structural, institutional, and political changes that took place during the 20th century. This chapter tracks the history of South Africa’s agricultural research and development system against this background, highlighting changes over the past 20 years. Such changes have enabled better documentation of public spending on R&D and assessments of changes in the methods by which those funds are disbursed.